Medulla oblongata damage and cardiac autonomic dysfunction in Parkinson disease. (13th December 2016) - Pyatigorskaya, Nadya; Mongin, Marie; Valabregue, Romain; Yahia-Cherif, Lydia; Ewenczyk, Claire; Poupon, Cyril; Debellemaniere, Eden; Vidailhet, Marie; Arnulf, Isabelle; Lehéricy, Stephane
Abstract : Objective: To characterize medulla oblongata damage using diffusion tensor imaging (DTI) in Parkinson disease (PD) and correlate it with dysfunction of the cardiac sympathetic/vagal balance. Methods: Fifty-two patients with PD and 24 healthy controls were included in the study. All participants underwent clinical examination and 3T MRI using 3D T1-weighted imaging and DTI. DTI metrics were calculated within manually drawn regions of interest. Heart rate variability was evaluated using spectral analysis of the R–R cardiac interval during REM and slow-wave sleep based on continuous overnight electrocardiographic monitoring. Respiratory frequency was measured in 30-second contiguous epochs of REM and slow-wave sleep. The relationships between imaging and cardiac variables were calculated using partial correlations followed by the multiple comparisons permutation approach. Results: The changes in heart rate and respiratory frequency variability from slow-wave sleep to REM sleep in healthy controls were no longer detectable in patients with PD. There were significant increases in the mean ( p = 0.006), axial ( p = 0.006), and radial diffusivities ( p = 0.005) in the medulla oblongata of patients with PD. In PD, diffusion changes were specifically correlated with a lower heart rate and respiratory frequency variability during REM sleep. Conclusions: This study provides evidence that medulla oblongata damage underlies cardiac sympathetic/vagal balance and respiratory dysfunction in patients with PD.